DNA capping agent control of electron transfer from silver nanoparticles - Tanner, E; Sokolov, S; Young, N; Compton, R (Royal Society of Chemistry, 2017)
Silver nanoparticles capped with either DNA or citrate are investigated electrochemically using stripping voltammetry and nano-impacts. Whilst the citrate capped particles are readily oxidised to silver cations at 0.7 V, the DNA capped particles undergo electron transfer from the silver core to the electrode in two distinct potential ranges - 0.8 to 1.1 V and 1.125 to 1.2 V, and only undergo complete oxidation at the higher potential range. These potentials reflect the oxidation of guanine and adenine respectively, with a potential sufficient to oxidise both base pairs being necessary to observe full silver oxidation. The DNA thus serves as a tunnelling barrier to electrically insulate the particle, and allows for selective oxidation to occur by controlling the potential applied.